The Role of Performance to Continue the Business for Nascent Entrepreneurs: The Effect of Entrepreneurial Self-Efficacy - Sanaji Sanaji (Journal of Business and Management Review, 2023)
High mortality rates and low entrepreneur ratios are problems in developing sustainable small businesses. Previous research has shown that entrepreneurial self-efficacy (ESE) is an important factor for increasing entrepreneurial intentions, but how ESE explains the continuity of business for nascent entrepreneurs is less researched. This study aims to investigate the role of business performance in explaining the relationship of ESE and career switching for nascent entrepreneur. Data were collected from nascent entrepreneur using questionnaires and analyzed by Partial Least Square-Structural Equation Modelling (PLS-SEM). The results of this study shown that ESE positively influence business performance. ESE and business performance negatively influence career switching intention for nascent entrepreneur. In summary, ESE can reinforce nascent entrepreneurs to continue and survive their business. Some theoreticals on entrepreneurship and practicals implication on entrepreneurship development are suggested in the rest of this paper.